A Smart Gym Framework: Theoretical Approach - Jain A. (My University, 2025)
In this paper, we propose a framework for a smart gym. The framework consists of a simple model and prototypes which can be implemented in a gym. The framework is basically an implementation of the smart city based on IOT. The foremost objective of the proposed framework is to develop an intrusive technology that will not only provide valuable and innovative services to the user by integrating the user and the smart devices but also provide an efficient utilization of the resources present in the gym. © 2015 IEEE.